A human right to culture and identity : the ambivalence of group rights - Mende, Janne (Studies in social and global justice., 2016)
Pursues the possibilities and limits of the UN's Declaration on the Rights of Indigenous Peoples by connecting theoretical discussions with empirical evidence, taken from extensive participant observation and on the qualitative content analysis of Indigenous and state documents.